Anne Willan: Reader’s Digest Complete Guide to Cookery - D, J.M. (Petits Propos Culinaires, 1990)
Anne Willan: Reader’s Digest Complete Guide to Cookery: Dorling, Kindersley, London, 1989: 528 pp, colour photographs, glossary, index, bibliography, £19.95.